Tourist Perceptions of Halal Tourism that Provides Tourist Satisfaction: a Case Study on Tourism in West Sumatra - Baby SM Poernomo; Mercy Spesa Devina de Fretes; Sukirno Sukirno; Nataya Premchaiporn (Yayasan Ilomata, 2022)
Indonesia as one of the countries with the largest Muslim population in the world has enormous potential to develop industry in the halal tourism sector. Halal tourism from year to year is growing continuously, considering the large number of Muslim tourists who travel but still prioritize the guidance of the Islamic religion. One of the regions in Indonesia that is encouraged to become a halal tourist destination is West Sumatra. However, until now, people's understanding of halal tourism is still different from one another. There are even some people who are worried that halal tourism is only for Muslims. This is a qualitative research with a case study approach. Data was collected by semi-structured interviews with 30 tourists, which were classified into domestic Muslim tourists, domestic non-Muslim tourists and foreign tourists. This is done in order to obtain data on how the perception of each tourist about halal tourism and what kind of halal tourism can provide tourist satisfaction. The result of this research shows that basically Muslim tourists, non-Muslims and foreign tourists agree with the implementation of halal tourism, especially in terms of halal food and drinks. Food does not contain pork or other non-halal ingredients and there is no non-halal activities or entertainments. The tourists also agree with the cleanliness factor, both in the object itself and the surrounding environment. However, there is still different perception among the informants regarding the dress code. Some Muslim tourists want visitors to wear clothes that are in accordance with Islamic ethics, while other visitors say that visitors are simply asked to dress modestly.